Transformasi Organisasional Privatisasi BUMN di Indonesia - KESI WIDJAJANTI (Jurnal Ekonomi dan Bisnis, 2009)
This study, aims to examine empirically, the best possible relationship among variables oforganizational transformation, competitive advantage and performance. The research objectis the state owned enterprise (SOEâ€™s) privatization in Indonesian. The analysis unit relatedto the research method, involves a company while the respondents occupied by the primarymanager.The method used for testing the empirical model is the Structural Equation Model onPartial Least Square. The strategic finding, taken from this research,implies in ways of achievingperformances. This reserch aimed to give theory implication on concept Resource BasedView will be meaningfull to create competitive advantage. Besides,the result gives managerialimplications that to improve performance need increasing organizational transformation toincrease competitive advantage. Creating competitive advantage can achive through directrole of organizational transformation. Related to the government policy, the government shouldattention resource in enterprises to become competitiveness as as mediating for successfultransformation organizational to increase performance. The future research should usedâ€œlongitudinalâ€ component to play important role on supporting this study.Keyword : Organizational Transformation, Competitive Advantage, Performance